Internal buckling in the prestrained laminated media - Konieczny, Sylwester; Woźniak, M.; Woźniak, Cz. (Wydawnictwo Politechniki Łódzkiej, 1997)
A new mathematical model for the internal stability analysis of multilayered periodic media is proposed. The apprach include the effect of lamina thickness on the global body behaviour. Some special results are discussed.
Keywords: wyboczenie wewnętrzne; analiza stabilności wewnętrznej; internal stability analysis; internal buckling